Contributions of fine mineral particles and active Al/Fe to stabilization of plant material in neutral-to-alkaline soils of Indo-Gangetic Plain - Ruohan Zhong; Han Lyu; Monika Kumari; Ajay Kumar Mishra; M.L. Jat; Randy A. Dahlgren; Shinya Funakawa; Tetsuhiro Watanabe (Geoderma, 2023)
Factors controlling organic carbon stabilization are elusive in neutral-to-alkaline soils, thereby hindering the assessment of carbon sequestration potential across vast agricultural regions like the Indo-Gangetic Plain (IGP). This study investigated controls over mineralization and stabilization of added organic matter in tropical neutral-to-alkaline soils with low organic carbon (SOC). Using topsoil and subsoil samples from 12 sites of upper-to-lower IGP, we conducted a one-year incubation with and without adding 13C-labeled maize material. We tracked CO2 release and residual C remaining in soil organic matter fractions (free, occluded particulate (oPOM), and mineral-associated organic matter (MAOM)) and analyzed organic matter molecular compositions in incubated soils using pyrolysis-GC/MS. Our results revealed that 48 ± 7 % of added maize C was mineralized, mostly within the first 70 days. Higher active Al/Fe, notably Al, retarded primary maize mineralization by facilitating aggregation. High SOC content and SOC saturation degree resulted in more maize mineralization. The disappearance of maize-unique compounds (e.g., neophytadiene) revealed substantial degradation of added maize. Regarding SOC composition, maize addition increased the relative abundance of fatty acids and decreased that of N-containing compounds. Most residual maize-derived C was found in stabilized fractions, MAOM (77 ± 15 % of residual maize C) and oPOM (8 ± 4 %). Clay fraction contributed to most maize-derived C stabilization as MAOM (path coefficient (β) = 0.81**). Moreover, the significant correlation (P < 0.001) between maize-derived oPOM C and active Al/Fe or clay + silt suggested that active Al/Fe contributed to the stabilization of maize-derived C as oPOM (β = 0.62***) probably by bonding clay and silt particles to form stable aggregates since active Al/Fe content was low (<14 cmol kg−1). Our study highlighted the importance of active Al/Fe in stabilizing SOC, by promoting aggregation and retarding degradation of residue-derived C in neutral-to-alkaline soils.